2012
DOI: 10.1371/journal.pone.0047115
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil Nanoparticles Inhibit Hepatocellular Carcinoma via Activation of the p53 Pathway in the Orthotopic Transplant Mouse Model

Abstract: Biodegradable polymer nanoparticle drug delivery systems provide targeted drug delivery, improved pharmacokinetic and biodistribution, enhanced drug stability and fewer side effects. These drug delivery systems are widely used for delivering cytotoxic agents. In the present study, we synthesized GC/5-FU nanoparticles by combining galactosylated chitosan (GC) material with 5-FU, and tested its effect on liver cancer in vitro and in vivo. The in vitro anti-cancer effects of this sustained release system were bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 48 publications
5
28
0
Order By: Relevance
“…Results showed that these GC/5-FU nanoparticles had obvious targeting properties against liver cancer, and that they may regulate the distribution and metabolism of 5-FU in vivo, thereby significantly reducing the toxic side effects of 5-FU. 20 In this study, we successfully synthesized the GCGA/5-FU nanoparticle, and its characteristics were observed in vitro and in vivo. This study used GCGA/5-FU nanoparticles to treat mice with liver cancer, and results showed that GCGA/5-FU nanoparticles significantly inhibited tumor growth and attenuated the immune suppression induced by 5-FU.…”
Section: Cheng Et Almentioning
confidence: 98%
See 1 more Smart Citation
“…Results showed that these GC/5-FU nanoparticles had obvious targeting properties against liver cancer, and that they may regulate the distribution and metabolism of 5-FU in vivo, thereby significantly reducing the toxic side effects of 5-FU. 20 In this study, we successfully synthesized the GCGA/5-FU nanoparticle, and its characteristics were observed in vitro and in vivo. This study used GCGA/5-FU nanoparticles to treat mice with liver cancer, and results showed that GCGA/5-FU nanoparticles significantly inhibited tumor growth and attenuated the immune suppression induced by 5-FU.…”
Section: Cheng Et Almentioning
confidence: 98%
“…20 Figure 2A shows that GCGA/5-FU nanoparticles had the highest liver concentration, which was 1.65, 2.35, and 2.75 times the concentrations of the GA-CTS/5-FU, CTS/5-FU, and 5-FU nanoparticles, respectively. However, the concentration of 5-FU in lung, spleen, heart, brain, and muscle tissues decreased from the 5-FU, CTS/5-FU, and GA-CTS/5-FU groups to the GCGA/5-FU group, and this trend was consistent with the results from confocal microscopy, as shown in Figure 2B.…”
mentioning
confidence: 99%
“…Other chemotherapeutic agents delivered using CSNPs include 5-fluorouracil (5-FU) and camptothecin (CPT) [53][54][55]. 5-FU is a cytotoxic drug, which interferes with nucleic acid synthesis, inhibits DNA synthesis and eventually halts cell growth [56].…”
Section: Chitosanmentioning
confidence: 99%
“…We found that the GC/5-FU nanoparticles specifically target the liver and liver cancer cells, and that the deficiency of GC/5-FU nanoparticles increased the concentration of 5-FU in normal liver tissues [18]. Therefore, we synthesized nanomaterials targeting liver cancer based on preliminary research that aimed to improve liver cancer targeting and reduce the drug concentrations in liver tissue.…”
Section: Introductionmentioning
confidence: 99%